Mutational Landscapes and Phenotypic Spectrum of SWI/SNF-Related Intellectual Disability Disorders - Bögershausen, Nina; Wollnik, Bernd (Frontiers in Molecular Neuroscience, 2018)
Mutations in genes that encode proteins of the SWI/SNF complex, called BAF complex in mammals, cause a spectrum of disorders that ranges from syndromic intellectual disability to Coffin-Siris syndrome (CSS) to Nicolaides-Baraitser syndrome (NCBRS). While NCBRS is known to be a recognizable and restricted phenotype, caused by missense mutations in SMARCA2, the term Coffin-Siris syndrome has been used lately for a more heterogeneous group of phenotypes that are caused by mutations in either of the genes ARID1B, ARID1A, ARID2, SMARCA4, SMARCB1, SMARCE1, SOX11 or DPF2. In this review, we summarize the current knowledge on the phenotypic traits and molecular causes of the above named conditions, consider the question whether a clinical distinction of the phenotypes is still adequate, and suggest the term “SWI/SNF-related intellectual disability disorders” (SSRIDD). We will also outline important features to identify the ARID1B-related phenotype in the absence of classic CSS features, and discuss distinctive and overlapping features of the SSRIDD subtypes. Moreover, we will briefly review the function of the SWI/SNF complex in development and describe the mutational landscapes of the genes involved in SSRIDD.